2020
DOI: 10.1002/cta.2737
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond nonlinear model predictive control for DC‐DC converters

Abstract: Summary In this paper, we present a novel nonlinear model predictive control (NMPC) formulation for the transient control of a DC‐DC converter. We demonstrate that a real‐time implementation of the proposed NMPC scheme using the PANOC solver can be efficiently applied to control DC‐DC converters in the microsecond range. Moreover, an embedded, code‐generated version of PANOC can be implemented using microcontrollers or digital signal processors. The algorithm is incorporated in the transient simulator of PWM D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…(4) In contrast, the grounding resistance change has an insignificant impact on insulator flashover in the case of shielding failure. (5) The study offers a research platform for the identification of back-flashover and shielding-failure phenomena and enables the straightforward evaluation of the lightning performance of the HVDC transmission systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) In contrast, the grounding resistance change has an insignificant impact on insulator flashover in the case of shielding failure. (5) The study offers a research platform for the identification of back-flashover and shielding-failure phenomena and enables the straightforward evaluation of the lightning performance of the HVDC transmission systems.…”
Section: Discussionmentioning
confidence: 99%
“…Transportation of a large amount of power over long distances (≥500 km) results in problems such as reduction of power transfer, generation of reactive power and voltage profile variation [3]. Therefore, HVDC transmission is considered an optimal solution for connecting large-scale offshore renewable energy sources such as wind farms to power grids and linking distant generation sources with load centers [4,5]. Other benefits can be achieved by HVDC transmission systems, such as interconnection between unsynchronized AC systems, improving system stability and lower transmission line costs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The delays in reaching the convergence, due to model inaccuracies, were lower than 2 ms in the considered scenarios. This suggested that the proposed observer could be possibly exploited for current mode control of SMPS or for more sophisticate model-based control strategies such as model predictive control [26]. The main drawback of this approach was the computational effort, which was strongly reduced with respect to [21], due to the analytical formulation, but was still high for a low-cost microcontroller (e.g., the STM32F4 exploited in this work).…”
Section: Discussionmentioning
confidence: 99%
“…This makes the MPC an effective control tool in the power management scheme of the AC-DC MGs, power electronic converters and drives applications, wind power applications, and converter control in DC and AC MGs. 24,[26][27][28] Further, the FCS-MPC approach would achieve faster dynamics for current tracking and better steady-state responses and accessible digital implementation. 29 Owing to the above features, this paper investigates the FCS-MPC as a current tracking controller for associated power converters control.…”
Section: Introductionmentioning
confidence: 99%